2020
DOI: 10.4167/jbv.2020.50.4.203
|View full text |Cite
|
Sign up to set email alerts
|

The Roles of Chemokines in Immune Response to Mycobacterial Infection

Abstract: Tuberculosis (TB), a global and deadly infectious disease caused by Mycobacterium tuberculosis (Mtb), is manifested with host immune reaction. The balanced regulation between protective immune and pathologic inflammatory responses is critical to control progression to TB. Chemokines are a large family of cytokines that play an essential role for chemotaxis of immune and inflammatory cells to the sites of infection. Numerous chemokines including CXCL10 were reported as potential biomarkers of various stages of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
(85 reference statements)
1
2
0
Order By: Relevance
“…Our results demonstrated two main findings: (i) differential levels between groups (moderate increase in LTB, high in DS-TB, and extremely high in DR-TB) compared to HC and (ii) chemokines (CXCL10, CXCL9 and CXCL1) as the promising biomarker signature. These findings correlate with the previous postulations as both CXCL10 and CXCL9 and their elevated levels has been considered as potent diagnostic markers for both pulmonary and extrapulmonary TB 2 , 25 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our results demonstrated two main findings: (i) differential levels between groups (moderate increase in LTB, high in DS-TB, and extremely high in DR-TB) compared to HC and (ii) chemokines (CXCL10, CXCL9 and CXCL1) as the promising biomarker signature. These findings correlate with the previous postulations as both CXCL10 and CXCL9 and their elevated levels has been considered as potent diagnostic markers for both pulmonary and extrapulmonary TB 2 , 25 , 30 , 31 .…”
Section: Discussionsupporting
confidence: 90%
“…Chemokines are the kick-starters of innate and adaptive immune responses by their chemotactic effects 1 , 2 . Numerous animal studies delineated the host protective and detrimental responses of chemokine ligands and their receptors during tuberculosis (TB).…”
Section: Introductionmentioning
confidence: 99%
“…In this study, many of the inflammatory cytokines that would be expected as part of an innate response to Mtb such as Il-6, IL-1α and Il-1β and TNF-α, and were found in the vitreous, and that in primed vitreous the concentrations were generally higher than in unprimed vitreous ( Paik et al, 2020 ; Cooper et al, 2011 ). In human eyes with presumed TB associated uveitis, and chronic idiopathic uveitis, many of the same cytokines that were identified in this study including IP-10, IL-12, VEGF, MCP-1, MIP-1α, and MIP-1β have been identified ( Errera et al, 2022 ; Curnow et al, 2005 ; El-Asrar et al, 2011 ; Xu et al, 2020 ; Nagata et al, 2012 ; Chen et al, 2015 ; Zhao et al, 2015 ; Fukunaga et al, 2020 ).…”
Section: Discussionmentioning
confidence: 54%